Botanic Garden Profile Inverewe: gardening on the edge - Frediani, Kevin (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2020)
Set in the heart of the Scottish Highlands, Inverewe is one of the most spectacular garden locations in the UK. Situated beside the A382 on the North Coast 500 tourist route, the property receives over 100,000 visitors each year, drawn to see a diversity of plants and to enjoy the breathtaking backdrop of mountains and seascape it affords. Since its first plantings in 1864, the property has been a centre for experimental approaches to establishing and growing tender woody and herbaceous perennials, while a diaspora of alumni have gone on to fulfil prominent roles in the horticultural industry over the years. The garden today covers approximately 22 ha of mainly woodland gardens, renowned for the diversity of their designed elements and whose conservation management is based on a thorough understanding, appreciation and analysis of the garden’s historical development and its significance in local, regional and national contexts.In recent years, Inverewe has faced a number of challenges related to the growing impact of global change, with increased occurrences of extreme weather events, and emergent pest and disease incidents associated with climate change and the movement of plants and their vectors, which include human-aided transport of problems between sites. In this context, this article provides a lens on the drivers of change that the plant collection is facing in the early decades of the 21st century. After an introduction to the garden, its evolved collections and management approach, three case studies are highlighted as examples of emerging threats to Inverewe as a garden and work of art. Inverewe is presented as a landscape that endures through adaptation to social, economic and, increasingly, environmental challenges that shape the direction it takes as a garden and plant collection growing on the edge.